The Influence of Colour Trap to The Community Structure on Apple Plant in Junggo, Tulungrejo Village, Bumiaji District, Batu City (Preliminary Study About Armoured Scale (Diaspididae family)) - Sama' Iradat Tito; Gatot Mudjiono; Abdul Latief Abadi; Toto Himawan (Graduate Program, 2019)
Scales have attacked 9 hectares of apple land spread in 8 villages of Bumiaji sub-district such as Giripurno village, Tulungrejo village, Pandanrejo village, Sumbergondo village, Bulukerto village, Punten village, Gunungsari village, and Bumiaji village. This pest is a perennial pest on apple crops and difficult to control. The current way of control has not been able to overcome this pest problem. Therefore, research is needed to get effective control technology and easy to implement. The use of colour traps in addition to control needs, and also expected to needs of monitoring and identification of existing problems that make this pest difficult to control. This research was conducted to find out the effect of colour trap to community structure at Junggo, Tulungrejo Village, Bumiaji Sub-district, Batu City. Colour traps are fitted with 10 types of treatment colour with 3 replication. The observational data were analyzed by using community test. The results showed that the community analysis on the colour trap indicating that the index of diversity (H') and the dominance index (C) all treatments and families were small but the uniformity index (E) belonged to the stable community was owned by treatment B8 white colour with height 1.5m) and B9 (clear colour with height 1m). The largest dominant index (C) data of Diaspididae family (scales) is owned by B7 treatment (white colour with height 1m) of 0.18. The natural enemy species of scales found on apple plants is Encarsia strenua (silvestri) : Famili Aphelinidae.Key Words: Apple, Colour trap, Scales